Atravessamentos visuais e arteiras infâncias - Duran, Gisele Caroline Ruiz (Universidade Federal de São Carlos, 2020)
We live in times characterized by the ubiquity of images, which are exposed to us excessively every day. The children of times like these are already born immersed in this imagetic world, which educates, teaches, models and produces bodies, subjects and ways of life. The image, especially photography, is reflected in this work from the intersection between the researcher's experiences and subjectivities, the experiences lived with children in photographic workshops, the images produced by them and the thoughts of several authors who have studied the technique and photographic art. It seeks to establish montages: relationships, approximations and distances between experiences, memories, thoughts, fragments of writings and images; create tensions, voids and gaps in the interpretive framework, learn and unlearn, and from these encounters and mismatches produce a type of knowledge aimed at creating and inventing new ways of looking, researching, teaching, learning, feeling and making images, within and out of school.
Visual crossings and crafty childhoods
Keywords: Imagem; Fotografia; Arte; Infância; Image; Photography; Art; Childhood; CIENCIAS HUMANAS::EDUCACAO